Application of High-voltage Circuit Breaker Status Evaluation Method Based on Primary and Secondary Integrated Switch Detection Platform. Issue 1 (1st December 2022) - Zhang, Xinyu; Nie, Yu; Zhao, Chuanzong; Du, Wei; Wang, Yanan; Cai, Zhiwei; Dong, Wenhai; Liu, Yanbing
Abstract: This paper proposes a high-voltage circuit breakers status evaluation method based on the primary and secondary integrated switch detection platform to cope with the poor effect of existing evaluation methods. A high-voltage circuit breaker status evaluation index system was determined in combination with the actual situation of high-voltage circuit breakers. The subjective weight of the status of the high-voltage circuit breaker was determined with the analytic hierarchy process, the objective weight of the status of the high-voltage circuit breaker was calculated by the entropy method, and the analog acquisition accuracy of the high-voltage circuit breaker was improved with the amplification circuit design of the genetic algorithm. After the weight was determined, the overall weighted evaluation was performed, and the status of the high-voltage circuit breaker was evaluated through primary and secondary integration. Through comparative experiments, it can be seen that the results of the weight proportion test on the high-voltage circuit breaker status evaluation based on the primary and secondary integration are greater than that of the traditional high-voltage circuit breaker status evaluation method. Therefore, the designed evaluation method based on the primary and secondary integration can be better applied to the distribution network and protect the circuit.